Varieties of housing finance in historical perspective: The impact of mortgage finance systems on urban structures and homeownership - Timothy Blackwell; Sebastian Kohl (Max Planck Institute for the Study of Societies, 2017)
In this paper, we argue that the complexion of housing finance systems in OECD countries, both now and historically, has a significant bearing on a number of core housing-related indicators, including housing form, tenure composition, and urban development. Existing literature in the fields of housing studies and comparative political economy, however, has often neglected the historical dynamics of housing finance, while contemporaneously, financial historians have focused almost exclusively on company and not mortgage finance. We identify four different "ideal types" of housing finance systems that developed in mature capitalist economies when organized housing finance institutions began to emerge throughout the long nineteenth century: informal person-to-person lending and state lending as solutions outside specialized banking circuits, and deposit-based and bond-based institutions as banking solutions. We adapt Alexander Gerschenkron's theory of economic backwardness in order to explain the temporal-spatial emergence of these distinct types. We draw a path-dependent conclusion, noting that the more countries developed bond-based mortgage banks in the nineteenth century, the more they tended towards multi-story building structure, low homeownership rates and lower securitization levels in the twentieth century. A collection of unique historical city and country data supports these findings. – – In diesem Artikel behaupten wir, dass heutige und historische Wohnfinanzsysteme in OECD-Ländern einen starken Einfluss auf eine Reihe zentraler Wohnungsindikatoren wie die Bauform, die Wohneigentumsstruktur und die städtische Entwicklung hatten. Die Literatur des Wohnungswesens und der Vergleichenden Politischen Ökonomie hat die historische Wohnfinanzentwicklung bisher stiefmütterlich behandelt, während Finanzhistoriker sich fast ausschließlich auf Unternehmens- und nicht Hypothekenfinanzierung konzentriert haben. Wir identifizieren vier verschiedene Idealtypen der Wohnfinanzregime, die sich in entwickelten Ökonomien im Übergang zum organisierten Realkredit im langen 19. Jahrhundert entwickelten: informelle personale Kredite und Staatskredite als Typen außerhalb von Banken, einlagen- und pfandbrieffinanzierte Typen von Hypothekenbanken. Wir nutzen Alexander Gerschenkrons Theorie der ökonomischen Rückständigkeit, um die raumzeitlich unterschiedliche Entstehung dieser Typen zu erklären, und ziehen einen pfadabhängigen Schluss: Je mehr Länder im 19. Jahrhundert pfandbrieffinanzierte Hypothekenbanken entwickelten, desto mehr haben sie damals wie heute Mehrgeschossstädte und desto niedriger ist bis heute ihre Wohneigentumsquote sowie ihr Umlauf an hypothekenbesicherten Wertpapieren. Eine Sammlung historischer Stadt- und Finanzdaten stützt diese Befunde.
hdl:11858/00-001M-0000-002C-6801-F
Keywords: 300; housing finance; homeownership; building form; urbanization; Gerschenkron; path dependence; financial history; mortgage banks; building societies; buildings and loans; Hausfinanz; Wohneigentum; Bauform; Urbanisierung; Gerschenkron; Pfadabhängigkeit; Finanzgeschichte; Hypothekenbanken; Bausparkassen